2024
DOI: 10.3390/ijerph21040425
|View full text |Cite
|
Sign up to set email alerts
|

Relational Coordination at the Primary–Secondary Care Interface: Insights from a Cross-Sectional Survey in the South Tyrolean Healthcare System

Christian J. Wiedermann,
Verena Barbieri,
Adolf Engl
et al.

Abstract: Understanding the dynamics of teamwork and communication among healthcare professionals is crucial in the face of evolving healthcare challenges. This study assessed relational coordination among healthcare professionals in the South Tyrolean healthcare system in Italy, focusing on communication and teamwork dynamics in a cross-sectional survey. Using the validated Relational Coordination Survey (RCS) instrument and 525 completed online responses, the questionnaire aimed to understand the implications of diffe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Expanding on the implications of observed communication gaps in the present study, the findings are consistent with the documented weak relational coordination between GPs and HPs [17]. This weak coordination, characterized by low frequency and timeliness of communication, critically undermines the effective implementation of the HWG criteria and directly impacts referral efficiency and overall healthcare delivery.…”
Section: Communication and Collaborationsupporting
confidence: 87%
See 1 more Smart Citation
“…Expanding on the implications of observed communication gaps in the present study, the findings are consistent with the documented weak relational coordination between GPs and HPs [17]. This weak coordination, characterized by low frequency and timeliness of communication, critically undermines the effective implementation of the HWG criteria and directly impacts referral efficiency and overall healthcare delivery.…”
Section: Communication and Collaborationsupporting
confidence: 87%
“…This survey on an HWG was conducted as part of a broader study on relational coordination within South Tyrol's healthcare system. While relational coordination findings are detailed in a separate publication [17], this study focused exclusively on the exploration and analysis of an HWG. This distinction allows for a concentrated examination of HWG practices outside relational dynamics.…”
Section: Study Design and Settingmentioning
confidence: 99%
“…German-speaking districts showed stronger RC, probably due to greater linguistic homogeneity, which facilitates more effective communication within healthcare teams. The study showed a clear effect of language on between-group RC, suggesting that shared linguistic backgrounds strengthen RC, highlighting the importance of cultural and linguistic congruence in improving team dynamics and healthcare delivery [6].…”
Section: Job Satisfaction and Relational Coordinationmentioning
confidence: 83%
“…Building on the recently presented research [6], this study extends the exploration of RC among healthcare professionals within the SABES-ASAA. The first study assessed the status of RC among physicians, nurses, and administrators, laying the groundwork for understanding the broader impact of RC in diverse multilingual healthcare environments.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation